Tinjauan Yuridis Tindak Pidana Persetubuhan dengan Anak Dibawah Umur Berdasarkan Undang-undang Nomor 35 Tahun 2014 tentang Perlindungan Anak - Safira, Jihan; Nurhimmi Falahayati; Dian Mandayani Ananda Nasution (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The increasing incidence of sexual offences against minors constitutes a serious violation of children's rights as an integral part of human rights. Such crimes not only undermine children's dignity but also cause long-term psychological harm and disrupt their development. In response, the Indonesian government enacted Law No. 35 of 2014 on Child Protection, which strengthens previous regulations by imposing minimum and maximum criminal sanctions as well as aggravated penalties for offenders in positions of authority. This study examines the legal regulation of child sexual intercourse crimes under the law, analyses factors influencing sentencing, and evaluates its implementation in judicial practice. Employing normative legal research with a legislative approach and secondary data analysis, the findings indicate that although the legal framework reflects the principle of the best interests of the child, its enforcement faces challenges, including evidentiary limitations, sentencing disparities, and low public awareness in reporting cases. Therefore, strengthened synergy among law enforcement agencies, government institutions, and the community is essential to ensure effective and equitable child protection